2009
DOI: 10.1007/s10067-009-1328-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference and acceptability of calcium plus vitamin D3 supplementation: a randomised, open, cross-over trial

Abstract: Preference for a drug formulation is important in adherence to long-term medication for chronic illnesses such as osteoporosis. We investigated the preference for and acceptability of chewable tablet containing calcium and vitamin D (Calci Chew D3, Nycomed) compared to that of a sachet containing calcium and vitamin D3 (Cad, Will-Pharma). This open, randomised, cross-over trial was set up to compare the preference and acceptability of two calcium plus vitamin D3 formulations (both with 500 mg calcium and 400/4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Sachet was considered to be more time-consuming and more difficult to take than chewable tablets [ 132 , 133 ] Children and adults with phenylketonuria (aged 8–49 years) 11 of 12 participants preferred a ‘ready to drink’ liquid protein substitute formulation over powder. The liquid formulation was considered easy to take and more convenient to use in different environments than the powder [ 132 , 133 ] Dispersible and effervescent tablets Infants and children (aged 3 months to 5 years) 90 % of caregivers reported that zinc dispersible tablets were as acceptable to their children, or more so, as other medicines, while 84 % were willing to use the medicine again in the future [ 134 ] Children (aged 0–5 years) Acceptability and adherence to diarrhoea treatment was more favourable using zinc dispersible tablets. Almost 90 % of children received 10 days’ treatment and two-thirds completed the full 14 days, while only 6.5 % of caregivers reported administration problems (4 % reported vomiting and 2.5 % refusal to take) [ 135 ] Children (aged 4–8 years) A citrus-flavoured effervescent tablet was preferred over peppermint-flavoured syrup by more than two-thirds of the children and their caregivers [ 136 ] Parkinson’s disease patients with dysphagia The acceptability of a dispersible tablet containing levodopa-benserazide was considered advantageous with regard to ease of administration [ 137 ] ODTs Children (aged 6–11 years) More than 90 % of the children preferred strawberry-flavoured lansoprazole ODTs over peppermint-flavoured ranitidine syrup [ 138 ] Children (aged 5–11 years) The taste of the ondansetron ODTs scored lower than placebo; however, none of the children rejected or spat out the tablet and 87 % were reportedly willing to take it again in the future [ 139 ] Children (aged 6 months to 10 years) A randomised clinical trial involved administration of ondansetron ODTs or placebo to chi...…”
Section: Factors Affecting Acceptability Of Oral Liquid Dosage Formsmentioning
confidence: 99%
“…Sachet was considered to be more time-consuming and more difficult to take than chewable tablets [ 132 , 133 ] Children and adults with phenylketonuria (aged 8–49 years) 11 of 12 participants preferred a ‘ready to drink’ liquid protein substitute formulation over powder. The liquid formulation was considered easy to take and more convenient to use in different environments than the powder [ 132 , 133 ] Dispersible and effervescent tablets Infants and children (aged 3 months to 5 years) 90 % of caregivers reported that zinc dispersible tablets were as acceptable to their children, or more so, as other medicines, while 84 % were willing to use the medicine again in the future [ 134 ] Children (aged 0–5 years) Acceptability and adherence to diarrhoea treatment was more favourable using zinc dispersible tablets. Almost 90 % of children received 10 days’ treatment and two-thirds completed the full 14 days, while only 6.5 % of caregivers reported administration problems (4 % reported vomiting and 2.5 % refusal to take) [ 135 ] Children (aged 4–8 years) A citrus-flavoured effervescent tablet was preferred over peppermint-flavoured syrup by more than two-thirds of the children and their caregivers [ 136 ] Parkinson’s disease patients with dysphagia The acceptability of a dispersible tablet containing levodopa-benserazide was considered advantageous with regard to ease of administration [ 137 ] ODTs Children (aged 6–11 years) More than 90 % of the children preferred strawberry-flavoured lansoprazole ODTs over peppermint-flavoured ranitidine syrup [ 138 ] Children (aged 5–11 years) The taste of the ondansetron ODTs scored lower than placebo; however, none of the children rejected or spat out the tablet and 87 % were reportedly willing to take it again in the future [ 139 ] Children (aged 6 months to 10 years) A randomised clinical trial involved administration of ondansetron ODTs or placebo to chi...…”
Section: Factors Affecting Acceptability Of Oral Liquid Dosage Formsmentioning
confidence: 99%
“…Meta-analyses have also reported that compliance is also associated with insufficient social support, depression, and hopelessness. [5][6][7][8][9][10] In our study, no correlation was seen between regular use of Ca+vitD and age, perception of health state, level of activity, education, diagnosis of osteoporosis, osteoporosis treatment, or fracture history.…”
Section: Discussionmentioning
confidence: 74%
“…were reported to be the most common side effects. [8,9] Brunner et al found that only 23% of the female patients adhered to Ca+vitD treatment in the first year of osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the currently approved formulation of Calcichew D3 is preferred to Adcal-D3, a chewable tablet competitor product 24 , and it is also preferred to effervescent powder formulations 25,26 . However, since long-term adherence to supplements is generally low, new formulations are constantly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Non-adherence is linked to an increased fracture risk 7,22 and doubling of the cost per quality-adjusted life year (QALY) 23 . The formulation, size and taste of the supplement affects patients adherence 24 and therefore long-term clinical benefits to patients 25 .…”
Section: Introductionmentioning
confidence: 99%